An investigation on the mechanical properties of friction stir welded polycarbonate/aluminium oxide nanocomposite sheets. (October 2017) - Doniavi, Ali; Babazadeh, Saeedeh; Azdast, Taher; Hasanzadeh, Rezgar
Although considerable progress has been made in recent years in field of polymer welding, challenges still remain in using a friction stir welding method to join polycarbonate (PC) composites. This research provides an investigation on the effect of welding parameters (tool's travel and rotational speeds) on mechanical properties of PC nanocomposite weld lines. PC nanocomposites were prepared with different percentages of Al2 O3 nanofiller using a twin screw extruder and injection moulded as sheets in order to ease the welding. Considering various parameters and their levels, optimization of Taguchi experimental design was carried out, an L 16 orthogonal standard array was selected and the effective parameter was calculated using analysis of variance of the results. The results indicated that nanoalumina percentage is the most effective parameter on the tensile strength of weld and tool's travel speed and rotational speed are next effective parameters, respectively. According to signal-to-noise ratio, maximum weld tensile strength (89.5% of base material) is revealed when nanoalumina percentage, tool's travel speed and tool's rotational speed were chosen as 1 wt%, 12 mm/min and 1250 r/min, respectively.